ЎЗБЕК ВА ҚИРҒИЗ ТИЛЛАРИ ЛЕКСИКАСИДА МАКОН СЕМАЛИ ЛЕКСЕМАЛАРНИНГ ИФОДАЛАНИШИ (Scientific journal of the Fergana State University, 2023)
The given article describes similar and distinctive features of lexemes with seme “space” in Uzbek and Kyrgуz languages